Changing Trends in, and Characteristics Associated with, Not Undergoing Cardiac Catheterization in Elderly Adults Hospitalized with ST‐Segment Elevation Acute Myocardial Infarction. Issue 5 (4th May 2015) - Tisminetzky, Mayra; Erskine, Nathaniel; Chen, Han‐Yang; Gore, Joel; Gurwitz, Jerry; Yarzebski, Jorge; Joffe, Samuel; Shaw, Peter; Goldberg, Robert
<x xml:space="preserve">Abstract</x> Objectives To describe decade‐ long trends (1999–2009) in the rates of not undergoing cardiac catheterization and percutaneous coronary intervention (PCI) in individuals aged 65 and older presenting with an ST‐segment elevation acute myocardial infarction (STEMI) and factors associated with not undergoing these procedures. Design Observational population‐based study. Setting Worcester, Massachusetts, metropolitan area. Participants Individuals aged 65 and older hospitalized for an STEMI in six biennial periods between 1999 and 2009 at 11 central Massachusetts medical centers (N = 960). Measurements Analyses were conducted to examine the characteristics of people who did not undergo cardiac catheterization overall and stratified into two age strata (65–74, ≥75). Results Between 1999 and 2009, dramatic declines (from 59.4% to 7.5%) were observed in the proportion of older adults who did not undergo cardiac catheterization at all greater Worcester hospitals. These declines were observed in individuals aged 65 to 74 (58.4–6.7%) and in those aged 75 and older (69.4–13.5%). The proportion of individuals not undergoing PCI after undergoing cardiac catheterization decreased from 36.6% in 1999 to 6.5% in 2009. Women, individuals with a prior MI, those with do‐not‐resuscitate orders, and those with various comorbidities were less likely to have undergone these procedures than comparison groups. Conclusion Older adults who develop an STEMI are increasingly likely to undergo cardiac catheterization and PCI, but several high‐risk groups remain less likely to undergo these procedures.